Genetic Diversity of Ramie (Boehmeria Nivea L. Gaudich.) Originating from Wonosobo and Malang Based on Simple Sequence Repeat (SSR) Molecular Markers - Annisa, Annisa; Pangestu, Widya Nur; Kusmoro, Joko; Irawan, Budi (PLANTA TROPIKA, 2024)
Ramie has been widely used as a fiber crop for over 4000 years. The fibers are durable, white in color, and smooth in texture. Information on genetic diversity is important for selecting good breeding materials to produce superior offspring. This study aimed at determining the genetic diversity of Boehmeria nivea (L.) Gaudich. from Wonosobo and Malang using SSR as molecular markers. Nineteen accessions of ramie were analyzed for genetic diversity using 9 SSRs located adjacent to the gene associated with fiber yield traits. This study included the DNA extraction, amplification, and visualization of amplification. Data analysis included the allele number, frequency, PIC value, heterozygosity, Shannon information index, and AMOVA analysis. The results showed 229 alleles, with an average polymorphic percentage of 68.67%, the average allele frequency ranging from 0.07 to 0.11, an average PIC value of 0.84, and Jaccard's similarity score of 0-0.18. The He and Ho values in both populations were 0.719 and 0.278, respectively. AMOVA analysis revealed that 88% of the observed molecular variance was due to genetic differences within the population, whereas 12% of genetic variation was partitioned between populations. The present study showed high genetic diversity between Wonosobo and Malang ramie. This finding might support further programs for the fiber and biomaterial industry.